Smart Urban Data Space for Citizen Science - Bornholdt, Heiko; Jost, David; Kisters, Philipp; Rottleuthner, Michel; Shafeeq, Sehrish; Lamersdorf, Winfried; Schmidt, Thomas; Fischer, Mathias (Electronic Communications of the EASST, 2021)
In smart cities, the number of citizen-operated sensor devices continues to increase. This development multiplies the amount of collectible data about our urban environment. Currently, many of those sensors are connected to proprietary cloud services with questionable effects on user privacy. Simply avoiding interconnecting those devices misses out on opportunities to collectively use data as a shared source of information. The city of Hamburg sponsored project Smart Networks for Urban Citizen Participation (SANE) aims at enabling citizens to connect existing sensors to create a city-wide data space while keeping control of devices and gathered data. Interconnecting these sensors enables all citizens to generate higher value information and thus improve their urban environmental awareness. In this paper, we describe the demo of our SANE architecture. The demo presents how citizens connect to the city-wide data space, how data can be collected, processed, and shared in a privately manner.